Eating Habits and Lifestyle of the Executive Managers in Hierarchized Organizational Systems of Sport and Tourism - Agnieszka Gorka-CHOWANIEC; Kazimierz NAGODY-MROZOWICZ; Slawomir PATERAK (Communications of International Proceedings, 2020)
The diet and regularity of physical activity are two areas that determine a person's lifestyle and components of all health determinants. In turn, maintaining an individual's health at an appropriate level determines the effectiveness of his or her activities in both the private and professional sphere. The professional function of a manager is a profession characterized by high pressure of the environment, high professional mobility, high levels of stress and "non-standard" working time. The research concerned a socio-professional group of middle-level managers in hierarchical organizational systems of hospitality and sport. As a result of the sampling methodology adopted, the final sample size (GB) reached N = 107 observations. Two subgroups were identified in the study group: P1 n = 43 (sport managers/trainers) and P2 n = 67 (hotel managers/managers of four-star hotels). The selection of the sample was deliberate. Along with the increase in the assessment of the impact of diet, an increase in self-esteem of eating habits was noted (rtt = 0.391) and vice versa, the assessment of the impact of physical fitness on the effectiveness of work performed also increased (rtt = 0, 356); a strong and positive correlation was observed between opinions on eating habits and physical fitness of the subjects (rtt = 0.393); in the strong, positive and transitive correlationship relationship are also the physical fitness of the subjects and assessment of their impact on work efficiency (rtt = 0.380); the number of hours of professional work escalates the intensity of stress resulting from work (rtt = 0.359). nAs a result of our research, we can observe, in particular, that managers assess their eating habits as average. The study also showed that in the opinion of the analyzed group of respondents, the diet is determined by the effectiveness of their professional work.
Keywords: Lifestyle; Manager; Management; Sport; Tourism; Eating Habits.